2010
DOI: 10.1186/1752-0509-4-49
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing elementary mode analysis, pathway thermodynamics, and a genetic algorithm for metabolic flux determination and optimal metabolic network design

Abstract: BackgroundMicrobial hosts offer a number of unique advantages when used as production systems for both native and heterologous small-molecules. These advantages include high selectivity and benign environmental impact; however, a principal drawback is low yield and/or productivity, which limits economic viability. Therefore a major challenge in developing a microbial production system is to maximize formation of a specific product while sustaining cell growth. Tools to rationally reconfigure microbial metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 91 publications
0
25
0
Order By: Relevance
“…By using weights in the objective function it is possible to account for experimental difficulties in the implementation of the strain. This allows to prioritize biologically feasible MCS over infeasible ones and – in contrast to other, optimized based methods [9] – does not effect the ability to calculate the complete set. Taking biological feasibility into account seems advantageous as in our example we have demonstrated that due to the lacking gene-enzyme-reaction mapping roughly 70% of the predicted solutions would require the deletion of at least one non-enzymatic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…By using weights in the objective function it is possible to account for experimental difficulties in the implementation of the strain. This allows to prioritize biologically feasible MCS over infeasible ones and – in contrast to other, optimized based methods [9] – does not effect the ability to calculate the complete set. Taking biological feasibility into account seems advantageous as in our example we have demonstrated that due to the lacking gene-enzyme-reaction mapping roughly 70% of the predicted solutions would require the deletion of at least one non-enzymatic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…In this case thermodynamic constraints have played an important role narrowing the number of feasible pathways [55][56][57][58]. Although this approach is extremely useful, the main limitations are the relatively little thermodynamic information that is available for most pathway intermediates and the number of known biochemical pathways [57,59].…”
Section: Applying Thermodynamic Pathway Analysis In Strain Designmentioning
confidence: 99%
“…EFMs represent the network metabolic capabilities, however, the enumeration of EFMs is a cumbersome problem, thus, the reduction of EFMs to biologically relevant ones is an extremely useful approach. The first attempt of thermodynamic analysis of EFMs was realized to an E. coli metabolic network [48]. Later, a full NET analysis of EFMs was performed for a yeast model [49].…”
Section: Thermodynamics and Metabolomics Integration Into Metabolimentioning
confidence: 99%